PENGARUH PROGRAM PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Instituto Nacional da administração Publica Timor Leste) - Costa Henrques, Flavia Da (CITIZEN CHARTER, 2014)
ABSTRACT This study begins with the initial problems in government agencies, namely the Influence of Education and Training Employee Performance against Office of the Instituto Nacional da administração Publica East Timor. The problem has been the lack of effective measurement of the success of the Instituto Nacional da administração Publica (INAP) to provide education and training to employees as participants. Assessment of the performance of the employees should be done just before and after implementing training and education programs. However, to date assessment of the performance of the employees in the education and training center at the Instituto Nacional da Administração Publica (INAP) EastTimor is rarely done. The purose of this study is to determine how much education and training programs to give effect to the performance of employees at the Instituto Nacional da administração Publica (INAP) East Timor. The total sample of 35 people. The data analysis using sample regression test. data collection using questionnaires. The results showed a correlation value of 0.536, has a value of t greater than t table (3.645 > 1.6). Based on the hypothesis test, it can be stated Ho rejected and Ha accepted ,means a significant difference between training on employee performance at the Instituto Nacional da Administração Publica (INAP) East Timor. Keywords: Education and Training, Employee Performance